A percepção dos alunos da E.E.M. Gabriel Bezerra de Morais acerca dos conhecimentos básicos da matemática financeira - Ferreira, Francisco Ailton (2014)
The study on the subject Mathematical Finance presented here took into account the importance of the knowledge related to this area of mathematics plays in the lives of most people. We present the results of a survey of students of the 3rd Series of High School, about the basic content of financial mathematics. To do so, we started the study with brief considerations on the origin and evolution of money, followed by some relevant to Mathematical Finance basics and sequence we analyzed the level of perception of the student, as this basic knowledge, from the results generated applied research by students. We seek, therefore, arouses them to greater interest on such knowledge.